UPAYA MENINGKATKAN HASIL BELAJAR PASSING BAWAH SEPAKBOLA DENGAN ALAT BANTU - Richo David Christiawan; Budhi Satyawan; Tri Winarti Rahayu (PHEDHERAL, 2017)
The purpose of this study is to improve learning outcomes passing under football using learning aids on students of class XI Automotive 2 SMK PGRI 1 Surakarta academic year 2017/2018.This research is a classroom action research (PTK). Implemented in two cycles, with each cycle consisting of 2 meetings. The subjects of the study were students of class XI Automotive 2 SMK PGRI 1 Surakarta, amounting to 19 students consisting of 19 students son. Data source came from teachers, students and researchers. Data collection techniques are by observation and documentation or archive. Data validity test using triangulation valuation technique. Data analysis using quantitative descriptive technique using percentage technique to see trends that occur in learning activities.The results of data analysis can be submitted as follows: learning outcomes passing under the soccer of students on Cycle I of 19 students the percentage completeness 68.42% or as many as 13 students have entered the criteria complete and in Cycle II increased to 84.21% or as many as 16 students while 3 other students have not completed with KKM 75, while the target of completeness set by the researcher is 80%.The conclusion of this research is with the application of learning aids can improve learning outcomes passing under football in students of class XI Automotive 2 SMK PGRI 1 Surakarta.